2013
DOI: 10.5897/ajpp12.1449
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of organic acids and iridoid glycosides in traditional Chinese medicine (TCM) preparation reduning injection by rapid resolution liquid chromatography (RRLC) with ultraviolet (UV) detection under segmental monitoring mode

Abstract: A sensitive method of the simultaneous determination of organic acids and iridoid glycoside in reduning injection was described by rapid resolution liquid chromatography (RRLC) with ultraviolet (UV) detection under segmental monitoring mode. RRLC separation was achieved by use of a C 18 analytical column packed with sorbent of particle size 1.8 μm while the injected sample volume was set to 2 µl. A binary gradient elution program of aqueous phosphoric acid (0.1%, v/v) versus acetonitrile was selected for the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In China, it is widely used in clinical practice to reduce fever in viral infection diseases, such as serious influenza, infections of the upper respiratory tract and so on (Huang et al, 2006;Gao et al, 2011;Zhang, 2011;Sun et al, 2011). Phenolic acids and iridoid glycosides have been reported to be the principal components of Reduning injection (Zhu et al, 2013;Chang et al, 2013). Pharmacological studies have demonstrated that phenolic acids including neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid and isochlorogenic acid isomers have outstanding antioxidant, antibacterial, antiviral and antipyretic activity, and iridoid glycosides like geniposide have analgesic and anti-inflammatory effect (Chen et al, 2008;Mishima et al, 2005;Hung et al, 2006;Koo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In China, it is widely used in clinical practice to reduce fever in viral infection diseases, such as serious influenza, infections of the upper respiratory tract and so on (Huang et al, 2006;Gao et al, 2011;Zhang, 2011;Sun et al, 2011). Phenolic acids and iridoid glycosides have been reported to be the principal components of Reduning injection (Zhu et al, 2013;Chang et al, 2013). Pharmacological studies have demonstrated that phenolic acids including neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid and isochlorogenic acid isomers have outstanding antioxidant, antibacterial, antiviral and antipyretic activity, and iridoid glycosides like geniposide have analgesic and anti-inflammatory effect (Chen et al, 2008;Mishima et al, 2005;Hung et al, 2006;Koo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%